The Cosmic Microwave Background Radiation (CMBR) Anisotropy - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we will describe the Cosmic Microwave Background Radiation and its anisotropy. After describing the CMBR kinematics, we will see how primordial perturbations, in particular curvature perturbations, that were already observed, are described and propagate, and how they influence the CMBR.